Let [tex]x[/tex] be the distance between the base of the ladder and the bottom of the wall, and [tex]y[/tex] the distance between the top of the ladder and the bottom of the wall, so that
[tex]x^2+y^2=(25\,\mathrm{ft})^2[/tex]
Differentiate both sides with respect to time [tex]t[/tex]:
[tex]2x\dfrac{\mathrm dx}{\mathrm dt}+2y\dfrac{\mathrm dy}{\mathrm dt}=0[/tex]
When [tex]x=20\,\rm ft[/tex], the top of the ladder is
[tex]y=\sqrt{(25\,\mathrm{ft})^2-(20\,\mathrm{ft})^2}=15\,\mathrm{ft}[/tex]
above the ground. Then, given that the bottom of the ladder slides away from the wall at a rate of [tex]\dfrac{\mathrm dx}{\mathrm dt}=0.18\dfrac{\rm ft}{\rm s}[/tex], we have
[tex]2(20\,\mathrm{ft})\left(0.18\dfrac{\rm ft}{\rm s}\right)+2(15\,\mathrm{ft})\dfrac{\mathrm dy}{\mathrm dt}=0\implies\dfrac{\mathrm dy}{\mathrm dt}=-0.24\dfrac{\rm ft}{\rm s}[/tex]
That is, the top of the ladder is sliding downward at a rate of 0.24 ft/s.